Human immunodeficiency virus genetic variation that can escape cytotoxic T cell recognition. - Phillips, R; Rowland-Jones, S; Nixon, D; Gotch, F; Edwards, J; Ogunlesi, A; Elvin, J; Rothbard, J; Bangham, C; Rizza, C (1991)
In a longitudinal study of HIV seropositive patients, there were fluctuations in the specificity of cytotoxic T cells for the virus. This was matched by variability in proviral gag DNA epitope sequences in the lymphocytes of these patients. Some of these viral variants are not recognized by autologous T cells. Accumulation of such mutations in T-cell antigenic targets would provide a mechanism for immune escape.